Hubungan antara Loneliness dan Kecanduan Game Online pada Mahasiswa IAIT Kediri - Galuh Anggraini Perwira Sari; Uswatun Hasanah (Indonesian Journal of Islamic Education Studies (IJIES), 2020)
Online games are very popular among teenagers and adults, because there are many enthusiasts. If the players are constantly without self-control from teenagers and adults, they will become addicted to online games. Feeling lonely makes teens and adults vent through playing online games. This study aims to determine the relationship between Lonliness and Online Game Addiction in students who are not settled in a boarding house (Nduduk) at IAIT Kediri. With a sample of 40 students who did not settle in a boarding house (Nduduk), data collection was obtained from the results of a list of statements or questionnaires for Loneliness and Addiction to Online Games. This type of research is quantitative by using correlational research methods namely Product moment correlation analysis. Correlation test results obtained correlation coefficient values ​​of 0.556 Sig: 0.00 which means there is a relationship with the criteria being between the Loneliness variable with Addiction to Online Games.